Atributos químicos do solo, nutrição e crescimento de Eucalyptus Sp. na região sudoeste do Paraná - Dourado, Marcela Guedes (2021)
The forestry sector has been expanding every year and, with this growth, market demands for quality forest products increase, as well as the adoption of environmentally sound management practices that ensure the sustainability of forest production. The state of Paraná has an expressive contribution to the forestry sector, with 1.01 million hectares with forest plantations, of which about 255,844 hectares correspond to the Eucalyptus genus, representing 25.4% of its planted area. To achieve high forest productivity, the genetic material used and the nutritional conditions of the plants are important components related to wood production. Therefore, it is necessary to evaluate the relationship between soil chemical fertility and Eucalyptus sp. and the nutrient contents in the leaf tissue, thus identifying which soils are poorer and limit plant development. Therefore, the objective of the study was to evaluate the relationship of soil chemical attributes with the nutrition and growth of Eucalyptus sp. in Southwest Paraná. The study was carried out with foresters in the region, in five areas located in the municipalities of Cruzeiro do Iguaçu, Dois Vizinhos, Marmeleiro, Nova Esperança do Sudoeste and Salto do Lontra, whose main crop is eucalyptus, for the production of wood chips ( energy biomass), which are intended for the food industry to generate steam in boilers. The soil indicators that stood out the most in the areas were MOS, V%, P, K, Ca and Mg. Soil P, Mg and pH were the variables that most correlated with N, K, Ca, Na and Al contained in eucalyptus leaves. The variables DAP, HT, HDOM and Vcc (m³ ha-1) were the ones that most correlated with P, K, Ca, Mg, MOS, pH, CTC, V%, Fe and Cu of the soil and with B, Fe and Zn contained in eucalyptus leaves. The soil chemical attributes that most influenced PCA were P, MOS, pH and V%, being the attributes that most characterize soil fertility in areas 1, 2 and 3. The chemical attributes of soils that most contributed to the discriminant analysis in the three areas, they were CTC, pH, V(%), Cu, Fe and B. In the CCA analysis between the soil and foliar variables in area 1, with soils rich in MO and Fe, and in area 2 with soils rich in P, Cu, K, V(%) and pH showed no relationship with eucalyptus leaf nutrients.